1999
DOI: 10.1103/physrevlett.83.2433
|View full text |Cite
|
Sign up to set email alerts
|

Electric-Field Tuning of Spin-Dependent Exciton-Exciton Interactions in Coupled Quantum Wells

Abstract: We have shown experimentally that an electric field decreases the energy separation between the two components of a dense spin-polarized exciton gas in a coupled double quantum well, from a maximum splitting of ∼ 4 meV to zero, at a field of ∼35 kV/cm. This decrease, due to the fieldinduced deformation of the exciton wavefunction, is explained by an existing calculation of the change in the spin-dependent exciton-exciton interaction with the electron-hole separation. However, a new theory that considers the mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
3
12
0
Order By: Relevance
“…In a double well structure Aichmayr et al [14] detected an energy spin splitting dependence on the gate voltage that separated electrons and holes. As the voltage increased, the energy splitting decreased from 4 meV to zero.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a double well structure Aichmayr et al [14] detected an energy spin splitting dependence on the gate voltage that separated electrons and holes. As the voltage increased, the energy splitting decreased from 4 meV to zero.…”
Section: Discussionmentioning
confidence: 99%
“…A spontaneous energy splitting between the two different components of spin-polarized exciton gas in zero magnetic field was observed in multiple quantum wells [10][11][12][13] and in coupled quantum wells [14]. The splitting increased with the exciton density and decreased with the separation of the electron and hole induced by external electric field in coupled quantum wells.…”
Section: Introductionmentioning
confidence: 95%
“…It has revealed electronic spin flips through a multi-component decay in polarisation-resolved spectroscopy (characteristic timescales are in the range of tens to hundreds of picoseconds [1][2][3]5]). In coupled quantum wells (CQWs) where electrons and holes are spatially separated, the spin relaxation of indirect excitons has been found very different [11][12][13]. Experiments have shown that when prepared in a pure state (| ± 1 ), indirect excitons exhibit a very long-lived polarisation [14] with a time decay that can even exceed the radiative lifetime (≈ 100 ns), i.e.…”
Section: -P1mentioning
confidence: 99%
“…The hole spin relaxation time τ h s should satisfy 1/τ h s < δ exc /h, where δ exc is the electron-hole exchange energy. Application of the electrical bias reduces the exchange energy 22 , and the condition is no longer fulfilled. Indeed, at V g > 0.2 V the Kerr rotation decay becomes monotonous.…”
Section: Photoinduced Kerr Rotationmentioning
confidence: 99%